Self-medication prevalence and related factors among medical university students, 2015 - Kahnamouei-aghdam, Fariba; Zakeri, Anahita; Amani, Firouz; Sajjadifar, Mostafa; Mohammadi, Perham; Ojaghi, Habib (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Self-medication is one of the main health problems. Given the high prevalence of self-medicationin society and between students, the aim of this study was to assess the rate of self-medication among Ardabil medical students. Methods: This cross–sectional study has been done on 150 students which selected randomly from Ardabil Medical University Science students. Data collected by a questionnaire and then analyzed by statistical method in SPSS.19. Results: The rate of self-medication among students was 65%. Most of usage drug was sedatives with 77.1%. 7.2% of students were prepared drugs from places other than pharmacies and most of self-medication was the existence of drug free market with 71%. Conclusions: Given the high prevalence of self-medication among students it is necessary to promote a culture of drug use among students, education in the field of self-medication and its side effects are given to students.